Empirical antibacterial preventive treatment for preterm prelabour rupture of membranes occured between 22 and 34 weeks' gestation - T.S. Kotomina; A.D. Podtetenev; M.M. Burzhunova (LCC «Medicine-Inform», 2019)
T.S. Kotomina1, A.D. Podtetenev2, M.M. Burzhunova1 1City Clinical Hospital No. 52, Moscow, Russian Federation 2L.A. Vorokhobov City Clinical Hospital No. 67, Moscow, Russian Federation Aim: to improve the outcomes of pregnancy complicated with preterm prelabour rupture of membranes (PPROM) occured between 22 and 34 weeks' gestation by prescribing antibiotics which are highly effective against the most common microbes in these women. Patients and Methods: clinical laboratory tests were performed in 60 pregnant women with PPROM occured between 22 and 33 + 6 weeks' gestation. At admission, uterine secretion analysis and disc diffusion antibiotic susceptibility test were performed in a total of 60 women. Uterine secretion was introduced into the culture medium (blood agar 5% and Sabouraud dextrose agar). Microbial cultures were isolated and identified using standard methods. Results: in most cases of PPROM, high levels of bacterial contamination of uterine cavity with various microbial associations in high titers (≥105 CFU/ml) were revealed. Among them, the most common bacteria were Enterococcaceae and Enterobacteriaceae spp. Enterococcus faecalis and E. faecium were identified in 83% of uterine secretions, Escherichia coli and Klebsiella pneumoniae were common as well while Staphylococcus aureus and S. epidermidis, Streptococcus agalactiae and Str. bovis, Burkholderia cepacia, Еnterobacter cloacae, Candida spp. were uncommon. Antibiotic susceptibility test has demonstrated that third-generation cephalosporins (cefotaxime and ceftazidime but not ceftriaxone) are highly effective against the most common isolated microbes. Moreover, these antibiotics are approved for their use in the second and third trimesters of pregnancy. Conclusion: our findings demonstrate that cefotaxime is the first choice for empirical antibacterial treatment for PPROM occured between 22 and 34 weeks' gestation. Regimens of initial antibacterial preventive treatment for PPROM which were developed on the basis of antibiotic susceptibility test results improve pregnancy outcomes regardless of delivery method. Keywords: preterm prelabour rupture of membranes, preterm birth, antibacterial preventive treatment, antibiotic susceptibility. For citation: Kotomina T.S., Podtetenev A.D., Burzhunova M.M. Empirical antibacterial preventive treatment for preterm prelabour rupture of membranes occured between 22 and 34 weeks' gestation. Russian Journal of Woman and Child Health. 2019;2(3):177-181.